A Law and Social Work Clinical Program for the Elderly and Disabled: Past and Future Challenges - Toby Golick; Janet Lessem (Washington University Journal of Law & Policy, 2004)
This Essay tells the story of our effort to establish an interdisciplinary law and social work program at Cardozo Bet Tzedek Legal Services (“CBT”), a law clinic at Benjamin N. Cardozo School of Law. The program is predicated on the belief that law and social work collaboration will benefit clients as well as students. The Essay is primarily descriptive—telling what we did, why we did it, why we were disappointed with it, and how we changed the program. The Essay also attempts to continue a constructive critique, on the assumption that even if something is not broken, it can be made better.
Keywords: Clinical legal education; Social workers; Interdisciplinary approach in education